Melatonin Experiment: Exposing its Effects on Goat Physiology in Warming Conditions - Tanvi D, Vikram singh, Solomon Jebaraj (Revista Electronica de Veterinaria, 2024)
The welfare of cattle is threatened by climate change, especially in areas where temperatures are rising. The physiological traits of goats subjected to warmer temperatures are studied in this investigation to determine whether melatonin, a hormone renowned for regulating circadian cycles and stressful situations, can have any moderating impacts. Two goat groupings participated in a controlled study: Group 1 (G1) received melatonin nutrients, while Group 2 (G2) functioned as the untreated group. 50 female goats of the same weight and age were subjected to high heats (36°C and 42°C) for a total of five hours/day for five days in a row after being acclimated for four days at 26°C. During the course of the trial, 0.1 mg/kg of melatonin was injected at midday. Pre and post-melatonin treatment reactions are determined. The concentrations of hormones (T-4 and cortisol) and the proportion of each of genes associated with stress (ubiquitin and HSP-60) in mononuclear cells from the peripheral bloodstream have been evaluated in samples of blood drawn on different days. The findings demonstrated that as exposure temperatures rose in both G1 and G2, there was a substantial increase in rectal temperature and the rate of pulse. T-4 rates in the G1 decreased at 42°C, whereas cortisol levels in the G2 soared with exposure heat but kept decreasing in the G1. HSP-60 and other stress-associated genes were up-regulated in G1, especially at 42°C. In summary, reduced cortisol levels and increased expression of stress-associated genes suggested that melatonin had a cooling as well as cell-protective effect on goats in heated environments.